Health promotion focusing on migrant women through a community based participatory research approach - Cecilia Lindsjö; Katarina Sjögren Forss; Christine Kumlien; Margareta Rämgård (BMC, 2021)
Abstract Background Migrants are often more vulnerable to health issues compared to host populations, and particularly the women. Therefore, migrant women's health is important in promoting health equity in society. Participation and empowerment are central concepts in health promotion and in community-based participatory research aimed at enhancing health. The aim of this study was to identify conditions for health promotion together with women migrants through a community-based participatory research approach. Methods A community-based participatory research approach was applied in the programme Collaborative Innovations for Health Promotion in a socially disadvantaged area in Malmö, Sweden, where this study was conducted. Residents in the area were invited to participate in the research process on health promotion. Health promoters were recruited to the programme to encourage participation and a group of 21 migrant women participating in the programme were included in this study. A qualitative method was used for the data collection, namely, the story-dialogue method, where a process involving issue, reflections and actions guided the dialogues. The material was partly analysed together with the women, inspired by the second-level synthesis. Results Two main health issues, mental health and long-term pain, were reflected upon during the dialogues, and two main themes were elaborated in the process of analysis: Prioritising spare time to promote mental health and Collaboration to address healthcare dissatisfaction related to long-term pain. The women shared that they wanted to learn more about the healthcare system, and how to complain about it, and they also saw the togetherness as a strategy along the way. A decision was made to start a health circle in the community to continue collaboration on health promotion. Conclusions The community-based participatory research approach and the story dialogues constituted an essential foundation for the empowerment process. The health circle provides a forum for further work on conditions for health promotion, as a tool to support migrant women's health.